Optimal Tax-Transfer-Schemes under Partial Information - Stefan Homburg; Tim Lohse (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2004)
According to a widely held belief, ?all who are able to work, should work?. We consider this statement within a framework of non-linear taxation. The crucial difference between our model and the standard model is that the government can distinguish between productive persons and the disabled. A general proposition regarding the design of tax-transfer-schemes under such partial information is derived. Moreover, it is shown that unemployment on the side of the productive poor may still be optimal.
Keywords: H21; I38; 330; Optimal Taxation; Employment; Poverty; Welfare